PEMBERDAYAAN USAHA EKONOMI PRODUKTIF (UEP) BAGI MASYARAKAT MISKIN DI KECAMATAN MIOMAFFO TIMOR KABUPATEN TIMOR TENGAH UTARA (TTU) - Ghawa Rado, Bernadus; Khristina Kiha, Emilia (EDUTECH CONSULTANT, 2019)
The purpose of service is Institutional Capacity Development and Productive Economic Business of the Joint Business Group. The service location is in the Esa Oesena Faculty in East Miomaffo District, Timor Tengah Utara Regency. Participants who were the object of the training in this service were members of the